Pengaruh Implementasi Standart Operating Procedure, Disiplin Kerja dan Komitmen Terhadap Kinerja Karyawan Pada UD. Konco Tani - Sariyanti, Via (Jurnal Cendekia Manajemen (JCM); Vol 1 No 2 (2023): July, 2023)
The study discusses the effect of implementation of standart operating procedure, work discipline and commitment on employee performance at UD Konco Tani. This study aims to determine and explain the result of the influence of implementation of SOP, work discipline and commitment. The sample of this research at UD Konco Tani , namely as many as 44 employees. The sampling technique uses non- probability sampling, namely saturated sampling. This analysis technique used is the classical assumption, multiple linear regression. The results of this study are that there is a positive and significant effect of standart operating procedure on employee performance whit a significant value of 0,001 < 0,05. There is a positive and significant effect of work discipline on employee performance whit a significant value of 0,002 < 0,05. There is a positive and significant effect of commitment on employee performance whit a significant value of 0,000 < 0,05. There is an effect of standart operating procedure, work discipline and commitment on employee performance whit a significant value of 0,000 < 0,05. Keywords: Standart Operating Procedure, Work Discipline, Commitment, Employee Performance